Pengaruh eDiplomacy dalam Normalisasi Hubungan Diplomatik Amerika Serikat - Kuba pada Masa Pemerintahan Barack Obama - Ginting, Tirsa Kristiani Br; Paramasatya, Satwika (Journal of International Relations, 2019)
The phenomenon of the use of modern technology such as internet, website, and social media network sites such as Facebook and Twitter bring forth a concept of Digital Diplomacy or eDiplomacy. Under the leadership of Barack Obama, United States, the country with the largest technological growth be a pioneer to implement eDiplomacy in leveraging U.S. foreign policy. Obama aligned with the mission to create a transparent government, so State Department of United States initiates the eDiplomacy implementation of 21st Century statecraft agenda. The United States eDiplomacy program was used to actualize one of Obama's campaign promises, that is the normalization of diplomatic relations with Cuba. History records that these two countries have been in dispute for almost the past 54 years. This research aims to explain how eDiplomacy is used as an instrument for normalizing diplomatic relations between the United States and Cuba using the public diplomacy concept by analyzing the various uses of media platforms and its implications. This research used qualitative research method with process-tracing data analysis method. This research concludes that eDiplomacy is one of the determinants factors in normalizing diplomatic relations between the United States and Cuba